Antioxidant Test of Red and Green Colored-Leaves Infusions of Pucuk Merah (Syzygium myrtifolium Walp.) with DPPH method - Desy Muliana Wenas; Putrisa Anggun Meilani; Herdini Herdini (Jurnal Penelitian Farmasi & Herbal, 2022)
Red and green leaves of the pucuk merah (Syzygium myrtifolium Walp.) contain flavonoids, saponins, and tannins which have the potential as antioxidants. The purpose is test out the antioxidant activity of red leaves and green leaves infusions of red shoots (S. myrtifolium). Test material is extracted using infusion method. The testing of antioxidant activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) method. The free radical concentration of DPPH was analyzed using UV-Vis spectrophotometer after addition of various concentrations of S. myrtifolium leaves infusion extracts. Various concentrations of S. myrtafolium leaves infusion extracts used were 20 ppm; 10 ppm; 5 ppm; 2.5 ppm; 1.25 ppm; 0.625 ppm. Vitamin C solutions as the positive control were prepared on 5; 2.5; 1.25; 0,625; 0.3125 ppm. The result of the experiment showed the thick red and green leaf extract has IC50 value of 11,130 ppm and 10,522 ppm. The antioxidant activity of green leaf extract is higher than the red leaf extract. Research on green leaves extract of S. myrtafolium is suggested for further research as anticancer.